Impact of Human–Animal Interactions on Psychological and Physiological Factors Associated With Veterinary School Students and Donkeys - Artemiou, Elpida; Hutchison, Pippa; Machado, Marcus; Ellis, Daria; Bradtke, Jennifer; Pereira, Mary Mauldin; Carter, Julia; Bergfelt, Don (Frontiers in Veterinary Science, 2021)
There has been an increased interest in evaluating human–animal interactions and assessing the mutual health and wellbeing. In this study, first-year female and male veterinary school students not paired (n = 58) or paired (n = 25) with immature (≤9 mo) donkeys (n = 13) were engaged in three different types of interactions (1st, hands-off remote learning, 2nd, hands-on passive learning, and 3rd, hands-on active learning) for 30 min each during Week 2 (Time 1), Weeks 5–8 (Time 2), and Week 12 (Time 3) over three, 15-week periods. Student psychological data involved the Penn State Worry Questionnaire (PSWQ) scores collected from the interactive (student-donkey pairs) and non-interactive (no student-donkey pairs) groups and modified Comfort from Companion Animals Scale (CCAS) scores collected from the interactive group during Times 1, 2, and 3. Donkey physiological data involved collection of saliva within 10 min pre- and post-interaction during Times 1, 2, and 3 in association with the different types of interactions for immunoanalysis of cortisol. There were no significant effects of the various times and types of interactions on CCAS scores. While there were no significant effects of group and types of interactions on PSWQ scores, there was an effect (P = 0.01) of time. Overall mean PSWQ scores were significantly lower during Week 12 versus Week 2. Correspondingly, while there were no effects pre- vs. post-interaction within or among times on saliva cortisol concentrations in donkeys, there was an effect (P = 0.02) of the type of interaction. Mean concentrations were significantly lower with the hands-on passive and hands-on active learning versus the hands-off remote learning. In conclusion, while this study provides preliminary evidence surrounding student donkey interactions, future studies are required with more comprehensive designs to clarify these benefits and better understand the advantages and challenges surrounding student-donkey interactions.